2007
DOI: 10.1104/pp.107.106336
|View full text |Cite
|
Sign up to set email alerts
|

Dual Role of the Plastid Terminal Oxidase in Tomato

Abstract: The plastid terminal oxidase (PTOX) is a plastoquinol oxidase whose absence in tomato (Solanum lycopersicum) results in the ghost (gh) phenotype characterized by variegated leaves (with green and bleached sectors) and by carotenoid-deficient ripe fruit. We show that PTOX deficiency leads to photobleaching in cotyledons exposed to high light primarily as a consequence of reduced ability to synthesize carotenoids in the gh mutant, which is consistent with the known role of PTOX as a phytoene desaturase cofactor.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
61
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 48 publications
8
61
0
Order By: Relevance
“…These observations in Orr Ds resemble the effects seen in fruits of the tomato ghost (gh) mutant when averted from light (Shahbazi et al, 2007). This mutant is impaired in the plastid terminal oxidase gene (PTOX).…”
Section: )mentioning
confidence: 56%
“…These observations in Orr Ds resemble the effects seen in fruits of the tomato ghost (gh) mutant when averted from light (Shahbazi et al, 2007). This mutant is impaired in the plastid terminal oxidase gene (PTOX).…”
Section: )mentioning
confidence: 56%
“…Since it has been confirmed that PTOX plays a role as a terminal oxidase and the carotenoid biosynthesis process is dependent on re-oxidation of the reduced PQ pool (Carol and Kuntz, 2001;Morstadt et al, 2002), the suggested role for PTOX in the latter process is not incompatible. Thus, inhibition of PTOX in both molecular (by mutation) and biochemical (by inhibitor) levels affects plant photosynthesis apparatus, and consequently, plants tolerance under environmental stress conditions (Shahbazi et al, 2007;Gamboa et al, 2009). However, although PTOX in the photosynthetic electron transport chain probably does not play a major role during photosynthesis under optimal conditions (Gamboa et al, 2009), it likely participates to the required flexibility of photosynthetic electron transfer reactions, when photosynthesis operates under unstable environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…during stress (20 -23). Consistent with this view, studies in tomato ghost (the ortholog of the Arabidopsis im mutant) reveal that lack of PTOX in young seedlings as well as in mature tomato leaves results in increased sensitivity to high light stress due to disturbances in the redox status of the plastoquinone pool (23). In contrast, in vivo chlorophyll fluorescence measurements reveal that modulating IMMUTANS expression and/or protein accumulation does not alter the flux of intersystem electrons during steady state photosynthesis in Arabidopsis nor does it afford photoprotection (17).…”
Section: Alternative Oxidase (Aox)mentioning
confidence: 48%
“…However, in contrast to early development, studies with im and with Arabidopsis PTOX overexpressor lines show that alterations in IMMUTANS expression and/or protein accumulation have no effect on electron flow during steady state photosynthesis in mature leaves (17). Interestingly, this does not appear to be the case in tomato, where recent studies in the ghost variegation mutant have demonstrated that PTOX activity is necessary in mature leaves, especially under high light conditions (23).…”
Section: Mechanism Of Im Variegation-im Is a Single Copy Gene Inmentioning
confidence: 96%
See 1 more Smart Citation